Improved aquaculture management practices and its impact on small-scale rural aquaculture farmers in Bangladesh - Haque, A.B.M.; Khan, Md. Akhtaruzzaman; Mokarrom, Hossain; Hossain, Md. Emdad; Nahiduzzaman, Md; Islam, Md Sayemul (Elsevier, 2025)
This study focuses on the adoption of Improved Aquaculture Management Practices (IAMP) to boost farm productivity and income, examining factors influencing adoption among small-scale aquaculture fish farming households. The research involved 1178 fish farmers practicing three (small-scale commercial aquaculture, Gher based farming and homestead aquaculture) different aquaculture production systems in Bangladesh. Among them, 715 received training on IAMP and support (fingerlings, feed etc.) from WorldFish, while 463 served as control farmers. Adoption levels were measured using the adoption quotient index, and the impact on productivity and income was estimated using propensity score matching (PSM). Results indicated that approximately 65% of project farmers fully adopted IAMP, with around 28% adopting it partially. The adoption quotient of project farmers exceeded that of control farmers. Fish productivity and income were significantly higher for project farmers in all three technologies, and as the level of adoption increased, their productivity significantly surpassed that of control farmers. The findings show that farmers training, participatory trials, guidebooks, and farmers' field days have significant impact on IAMP adoption levels. Thus, in order to ensure sustainable aquaculture production and income for Bangladesh's small-scale farmers, it is recommended that improved aquaculture management practices be prioritized in an attempt to mitigate the challenges caused by environmental and economic factors in the aquaculture sector.